GLUCOSE SENSORS BASED ON ELECTROCHEMICAL PROCESS: A REVIEW - ARJUN KISHORE; NANDAGOPAN G.L; MURUGAN MANAVALAN; MANSOOR ANI NAJEEB (International Journal of Pharma and Bio Sciences, 2013)
The modes of detection process in glucose sensor mainly rely on three processes namely: electrochemical process, optical process and combination process .Glucose sensors can be made with the help of nanotechnology and it can be useful in sensing the glucose level in pancreatic - β cells .These nanostructured materials and oxides are dugout for the growth of glucose sensors with extra stability and sensitivity. In glucose sensors different types of metal oxides used are ZnO, MnOâ‚‚, and TiOâ‚‚ etc. In terms of insulin it shows a major role in achievement in normoglycaemic state and rejecting hypoglycemic state. Diabetic mellitus is the major disease caused by the increased level of glucose. So the level of glucose can be sensored by the glucose sensor. This article summarizes the use of glucose sensors and the challenges of the glucose sensors in different stages.